Highly aligned growth of carbon nanotube forests with in-situ catalyst generation: A route to multifunctional basalt fibres. (15th August 2022) - Sarasini, Fabrizio; Tirillò, Jacopo; Lilli, Matteo; Bracciale, Maria Paola; Vullum, Per Erik; Berto, Filippo; De Bellis, Giovanni; Tamburrano, Alessio; Cavoto, Gianluca; Pandolfi, Francesco; Rago, Ilaria
Abstract: Hierarchical fabrics are gaining ever-growing practical interest, thanks to the possibility of combining different properties into a single textile, particularly useful for applications such as high-performance composites showing in situ structural health monitoring capabilities. In this study, homogeneously aligned carbon nanotube forests are directly grown on basalt fabrics by a fast (∼15 min) chemical vapour deposition process without any external catalyst addition providing, for the first time, a highly dense coverage of the underlying substrate. It is demonstrated by transmission electron microscopy that the direct growth of nanotubes on basalt fibres is catalysed by the microstructural segregation of ferrous iron and its subsequent reduction in hydrogen atmosphere to nanocrystalline metallic iron. It is shown that in situ growth requires a pre-treatment etching which can be conducted in mild basic or acidic conditions, achieving optimum performance with an alkaline attack, without compromising the tensile strength of the fibres. Post-growth Raman analysis shows characteristic features associated with high graphitic ordering which turn an intrinsically insulating substrate into an electrically conductive (∼260 S/m) fabric, thus suggesting the possibility to employ the newly engineered hierarchical fabric in all those applications where the combination of good mechanical properties and electrical conductivity is a key requirement.